GINGIVA CHANGES IN DIABETES MELLITUS PATIENTS: LITERATURE REVIEW - Uswatul Husnaini; Nasution, Badai Buana; ichwan, M (Universitas Batam, 2025)
Diabetes mellitus is a chronic metabolic disease that leads to oral complications generally, including changes and damage to the gingiva due to increased inflammation. The incidence of periodontal disease is two to three times higher compared to individuals without diabetes, which exacerbates gingival tissue damage and slows down healing. Hyperglycemia triggers the formation of advanced glycation end-products (AGEs), which increase the production of pro-inflammatory cytokines. This article aims to identify changes in the gingiva associated with diabetes mellitus. The method used is a literature review of articles published online through databases such as Google Scholar and PubMed. The analyzed articles are publications from 2019 to 2024, with a total of 21 articles meeting the inclusion criteria and relevant to the research objectives. The study results indicate that the interaction between hyperglycemia causes changes in the gingiva of diabetic patients, increased oxidative stress, and dysfunction in the immune system, which worsens inflammation and gingival tissue damage. Factors such as increased free radicals, impaired tissue healing due to vascular dysfunction, and decreased collagen production also contribute to the exacerbation of tissue damage, thereby increasing the risk of periodontal disease in patients with diabetes mellitus. Gingivitis and periodontitis are two common forms of periodontal disease caused by pathogenic biofilms around the teeth.